EVALUACION CLINICA DE 100 RESTAURACIONES CON AMALGAMA DE FASE DISPERSA - Lahoud S., Víctor (1999)
The present estudies consist in lo evaluate the clince efficience during 12 months of 100 restorantions with amalgan of Face Dispersa. The results Shows during 12 months of clinic evaluation, that of obturations conservation yours marginal integration, the resistence of the fracture was optimun and absence of Pigmentation and Corrosion in all studies cases.